Synthesis and evaluation of new guanidine-thiourea organocatalyst for the nitro-Michael reaction: Theoretical studies on mechanism and enantioselectivity - Shubina, Tatyana E.; Freund, Matthias; Schenker, Sebastian; Clark, Timothy; Tsogoeva, Svetlana B. (Beilstein Journal of Organic Chemistry, 2012)
A new guanidine-thiourea organocatalyst has been developed and applied as bifunctional organocatalyst in the Michael addition reaction of diethyl malonate to trans-β-nitrostyrene. Extensive DFT calculations, including solvent effects and dispersion corrections, as well as ab initio calculations provide a plausible description of the reaction mechanism.
Keywords: bifunctional organocatalyst; DFT calculations; guanidine-thiourea; Michael addition; organocatalysis; transition states

(untitled) - Ma, J.-A.; Cahard, D. (Angew. Chem., Int. Ed., 2004)

(untitled) - Shibasaki, M.; Yoshikawa, N. (Chem. Rev., 2002)

(untitled) - Gröger, H. (Chem.–Eur. J., 2001)

(untitled) - Shibasaki, M.; Sasai, H.; Arai, T. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Dalko, P. I.; Moisan, L. (Angew. Chem., Int. Ed., 2001)

Asymmetric Organocatalysis - From Biomimetic Concepts to Applications in Asymmetric Synthesis - Berkessel, A.; Groeger, H. (Wiley-VCH, 2004)

(untitled) - Pihko, P. M. (Angew. Chem., Int. Ed., 2004)

(untitled) - Seayad, J.; List, B. (Org. Biomol. Chem., 2005)

(untitled) - Schreiner, P. R. (Chem. Soc. Rev., 2003)

(untitled) - Takemoto, Y. (Org. Biomol. Chem., 2005)

(untitled) - Taylor, M. S.; Jacobsen, E. N. (Angew. Chem., Int. Ed., 2006)

(untitled) - Connon, S. J. (Chem.–Eur. J., 2006)

(untitled) - Doyle, A. G.; Jacobsen, E. N. (Chem. Rev., 2007)

(untitled) - Okino, T.; Hoashi, Y.; Takemoto, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Okino, T.; Nakamura, S.; Furukawa, T.; Takemoto, Y. (Org. Lett., 2004)

(untitled) - Maher, D. J.; Connon, S. J. (Tetrahedron Lett., 2004)

(untitled) - Fuerst, D. E.; Jacobsen, E. N. (J. Am. Chem. Soc., 2005)

(untitled) - Yoon, T. P.; Jacobsen, E. N. (Angew. Chem., Int. Ed., 2005)

(untitled) - Li, B.-J.; Jiang, L.; Liu, M.; Chen, Y.-C.; Ding, L.-S.; Wu, Y. (Synlett, 2005)

(untitled) - Hoashi, Y.; Okino, T.; Takemoto, Y. (Angew. Chem., Int. Ed., 2005)

(untitled) - Vakulya, B.; Varga, S.; Csampai, A.; Soos, T. (Org. Lett., 2005)

(untitled) - Okino, T.; Hoashi, Y.; Furukawa, T.; Xu, X.; Takemoto, Y. (J. Am. Chem. Soc., 2005)

(untitled) - McCooey, S. H.; Connon, S. J. (Angew. Chem., Int. Ed., 2005)

(untitled) - Berkessel, A.; Cleemann, F.; Mukherjee, S.; Müller, T. N.; Lex, J. (Angew. Chem., Int. Ed., 2005)

(untitled) - Berkessel, A.; Cleemann, F.; Mukherjee, S. (Angew. Chem., Int. Ed., 2005)

(untitled) - Berkessel, A.; Mukherjee, S.; Cleemann, F.; Müller, T. N.; Lex, J. (Chem. Commun., 2005)

(untitled) - Wang, J.; Li, H.; Yu, X.; Zu, L.; Wang, W. (Org. Lett., 2005)

(untitled) - Inokuma, T.; Hoashi, Y.; Takemoto, Y. (J. Am. Chem. Soc., 2006)

(untitled) - Xu, X.; Furukawa, T.; Okino, T.; Miyabe, H.; Takemoto, Y. (Chem.–Eur. J., 2006)

(untitled) - Marcelli, T.; van der Haas, R. N. S.; van Maarseveen, J. H.; Hiemstra, H. (Angew. Chem., Int. Ed., 2006)

(untitled) - Cao, Y.-J.; Lu, H.-H.; Lai, Y.-Y.; Lu, L.-Q.; Xiao, W.-J. (Synthesis, 2006)

(untitled) - Cao, C.-L.; Ye, M.-C.; Sun, X.-L.; Tang, Y. (Org. Lett., 2006)

(untitled) - Zuend, S. J.; Jacobsen, E. N. (J. Am. Chem. Soc., 2007)

(untitled) - Wang, B.; Wu, F.; Wang, Y.; Liu, X.; Deng, L. (J. Am. Chem. Soc., 2007)

(untitled) - Dinér, P.; Nielsen, M.; Bertelsen, S.; Niess, B.; Jørgensen, K. A. (Chem. Commun., 2007)

(untitled) - Tsogoeva, S. B.; Wei, S. (Chem. Commun., 2006)

(untitled) - Huang, H.; Jacobsen, E. N. (J. Am. Chem. Soc., 2006)

(untitled) - Yalalov, D. A.; Tsogoeva, S. B.; Schmatz, S. (Adv. Synth. Catal., 2006)

(untitled) - Lalonde, M. P.; Chen, Y.; Jacobsen, E. N. (Angew. Chem., Int. Ed., 2006)

(untitled) - Wei, S.; Yalalov, D. A.; Tsogoeva, S. B.; Schmatz, S. (Catal. Today, 2007)

(untitled) - Liu, K.; Cui, H.-F.; Nie, J.; Dong, K.-Y.; Li, X.-J.; Ma, J.-A. (Org. Lett., 2007)

(untitled) - Yalalov, D. A.; Tsogoeva, S. B.; Shubina, T. E.; Martynova, I. M.; Clark, T. (Angew. Chem., Int. Ed., 2008)

(untitled) - Tsogoeva, S. B.; Hateley, M. J.; Yalalov, D. A.; Meindl, K.; Weckbecker, C.; Huthmacher, K. (Bioorg. Med. Chem., 2005)

(untitled) - Tsogoeva, S. B.; Yalalov, D. A.; Hateley, M. J.; Weckbecker, C.; Huthmacher, K. (Eur. J. Org. Chem., 2005)

(untitled) - Berner, O. M.; Tedeschi, L.; Enders, D. (Eur. J. Org. Chem., 2002)

(untitled) - Tsogoeva, S. B. (Eur. J. Org. Chem., 2007)

(untitled) - Almasi, D.; Alonso, D. A.; Nájera, C. (Tetrahedron: Asymmetry, 2007)

Purification of Laboratory Chemicals - Armarego, W. L. F.; Chai, C. L. L. (Elsevier Science, 2003)

(untitled) - Ishikawa, T.; Kumamoto, T. (Synthesis, 2006)

(untitled) - Sohtome, Y.; Hashimoto, Y.; Nagasawa, K. (Adv. Synth. Catal., 2005)

(untitled) - Sohtome, Y.; Takemura, N.; Iguchi, T.; Hashimoto, Y.; Nagasawa, K. (Synlett, 2006)

(untitled) - Sohtome, Y.; Hashimoto, Y.; Nagasawa, K. (Eur. J. Org. Chem., 2006)

(untitled) - Sohtome, Y.; Takemura, N.; Takada, K.; Takagi, R.; Iguchi, T.; Nagasawa, K. (Chem.–Asian J., 2007)

(untitled) - Feichtinger, K.; Zapf, C.; Sings, H. L.; Goodman, M. (J. Org. Chem., 1998)

(untitled) - Dodd, D. S.; Wallace, O. B. (Tetrahedron Lett., 1998)

(untitled) - Ley, S. V.; Massi, A. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Hamza, A.; Schubert, G.; Soos, T.; Pápai, I. (J. Am. Chem. Soc., 2006)

VAMP, v9.0 (Computer-Chemie-Centrum, Universität Erlangen-Nürnberg, 2005)

(untitled) - Schenker, S.; Schneider, C.; Tsogoeva, S. B.; Clark, T. (J. Chem. Theory Comput., 2011)

(untitled) - He, X.; Fusti-Molnar, L.; Cui, G.; Merz, K. M., Jr (J. Phys. Chem. B, 2009)

(untitled) - Schreiner, P. R.; Chernish, L. V.; Gunchenko, P. A.; Tikhonchuk, E. Y.; Hausmann, H.; Serafin, M.; Schlecht, S.; Dahl, J. E. P.; Carlson, R. M. K.; Fokin, A. A. (Nature, 2011)

(untitled) - Grimme, S.; Schreiner, P. R. (Angew. Chem., Int. Ed., 2011)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - Sieffert, N.; Bühl, M. (Inorg. Chem., 2009)

(untitled) - Seebach, D.; Grošelj, U.; Schweizer, W. B.; Grimme, S.; Mück-Lichtenfeld, C. (Helv. Chim. Acta, 2010)

(untitled) - Møller, C.; Plesset, M. S. (Phys. Rev., 1934)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Perdew, J. P.; Burke, K.; Wang, Y. (Phys. Rev. B, 1996)

(untitled) - Perdew, J. P.; Chevary, J. A.; Vosko, S. H.; Jackson, K. A.; Pederson, M. R.; Singh, D. J.; Fiolhais, C. (Phys. Rev. B, 1992)

(untitled) - Ditchfield, R.; Hehre, W. J.; Pople, J. A. (J. Chem. Phys., 1971)

(untitled) - Hariharan, P. C.; Pople, J. A. (Theor. Chim. Acta, 1973)

(untitled) - Hariharan, P. C.; Pople, J. A. (Mol. Phys., 1974)

(untitled) - Hehre, W. J.; Ditchfield, R.; Pople, J. A. (J. Chem. Phys., 1972)

(untitled) - Gordon, M. S. (Chem. Phys. Lett., 1980)

(untitled) - Blaudeau, J.-P.; McGrath, M. P.; Curtiss, L. A.; Radom, L. (J. Chem. Phys., 1997)

(untitled) - Francl, M. M.; Pietro, W. J.; Hehre, W. J.; Binkley, J. S.; Gordon, M. S.; DeFrees, D. J.; Pople, J. A. (J. Chem. Phys., 1982)

(untitled) - Binning, R. C., Jr; Curtiss, L. A. (J. Comput. Chem., 1990)

(untitled) - Rassolov, V. A.; Pople, J. A.; Ratner, M. A.; Windus, T. L. (J. Chem. Phys., 1998)

(untitled) - Rassolov, V. A.; Ratner, M. A.; Pople, J. A.; Redfern, P. C.; Curtiss, L. A. (J. Comput. Chem., 2001)

(untitled) - Frisch, M. J.; Pople, J. A.; Binkley, J. S. (J. Chem. Phys., 1984)

Gaussian 03, Revision C.02 (Gaussian, Inc., 2004)

(untitled) - Gonzalez, C.; Schlegel, H. B. (J. Phys. Chem., 1990)

(untitled) - Gonzalez, C.; Schlegel, H. B. (J. Chem. Phys., 1989)

(untitled) - Foresman, J. B.; Keith, T. A.; Wiberg, K. B.; Snoonian, J.; Frisch, M. J. (J. Phys. Chem., 1996)

Orca, an ab initio, DFT and semiempirical SCF-MO package